Down-regulation of ATM/hnRNPK signaling reduces adriamycin resistance of myeloid leukemia - ZHANG Jinfang, ZHONG Mingyan, YANG Quan, FENG Bei, LI Xingdong (Jichu yixue yu linchuang)
Objective To explore the role of ATM/hnRNPK signaling in the adriamycin resistance of acute myeloid leukemia. Methods Expression of ATM was examined in the adriamycin resistant and sensitive leukemia cell strains with Western blot. ATM expression was down-regulated by RNAi and ATM inhibitor in the adriamycin resistant cell strains. Expression level of hnRNPK and LC3Ⅰ/Ⅱ was detected by Western blot and adriamycin sensitivity was measured by CCK8 assay before and after modulation of ATM expression. Results ATM was overexpressed in adriamycin resistant leukemia cell strains. The decreased expression of ATM restored the sensitivity to adriamycin. Expression level of LC3Ⅱ and hnRNPK was consistent with the modulation of ATM expression. Conclusions The ATM/hnRNPK signaling pathway may play a role in the occurrence of adriamycin resistance in acute myeloid leukemia by regulating autophagy.